Hypnobirthing Berpengaruh Terhadap Penurunan Tingkat Ansietas dan Peningkatan Kadar Oksitosin Pada Ibu Hamil - Mauludiyah, Zaida; Fitrianingtyas, Rizki (Malang Journal of Midwifery (MAJORY), 2023)
Pregnant women are vulnerable to stress which results in prenatal anxiety or depression. Therefore, safe and comfortable therapy is needed for pregnant women, one of which is hypnobirthing. The purpose of this study was to determine the effectiveness of hypnobirthing thru anxiety levels and oxytocin levels in pregnant women in Arjasa District, Jember Regency. This study used a quasi-experimental design with a pretest and posttest control group design approach. The total sample is 24 pregnant women, where before and after participating in hypnobirthing the level of anxiety and oxytocin levels will be measured. Pregnancy anxiety was measured using the Indonesian Hypnobirthing Distress Scale compiled by psychiatrists and psychologists at RSPAD Gatot Subroto, Jakarta, and to assess oxytocin levels, blood plasma samples were examined using the Human Oxytocin ELISA. The analysis in this study used the MANOVA test, and the results showed that hypnobirthing affected stress levels and oxytocin levels with a Sig value. the significance level of the relationship with the results is <0.001 and <0.001.. Mothers who practice hypnobirthing regularly will become more calm/relaxed and always think positively about this pregnancy, thereby reducing anxiety. Hypnobirthing stimulus that is positive and calming will increase oxytocin. This proves that hypnobirthing can reduce anxiety so that oxytocin levels increase.